2021
DOI: 10.3389/fimmu.2021.673690
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Function in Calcium Oxalate Kidney Stone Formation: A Systematic Review of Literature

Abstract: BackgroundThe global prevalence and recurrence rate of kidney stones is very high. Recent studies of Randall plaques and urinary components in vivo, and in vitro including gene manipulation, have attempted to reveal the pathogenesis of kidney stones. However, the evidence remains insufficient to facilitate the development of novel curative therapies. The involvement of renal and peripheral macrophages in inflammatory processes offers promise that might lead to the development of therapeutic targets. The presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 62 publications
2
38
0
Order By: Relevance
“…The polarization of macrophages has been recognized to be involved in the pathogenesis of kidney stones ( Taguchi et al, 2021 ). Taguchi et al (2016) found that M1-macrophage transfusion promoted kidney stone formation in hyperoxaluric mice and that M2-macrophage transfusion suppressed stone formation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The polarization of macrophages has been recognized to be involved in the pathogenesis of kidney stones ( Taguchi et al, 2021 ). Taguchi et al (2016) found that M1-macrophage transfusion promoted kidney stone formation in hyperoxaluric mice and that M2-macrophage transfusion suppressed stone formation.…”
Section: Discussionmentioning
confidence: 99%
“…Conventionally, the immune system plays a crucial role in the formation and pathogenesis of kidney stones. Throughout kidney stone development, CaOx crystals promote the secretion of inflammatory cytokines and chemokines, possibly recruiting various immune cells to renal interstitium, including neutrophils, macrophages, and T cells ( Zhu et al, 2019 ; Taguchi et al, 2021 ). The dysfunction of the immune microenvironment in the kidney could not only initiate adverse factors, but also further exacerbate kidney stone formation ( Khan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, SPP1 is a chemical attractant for macrophages, which could regulate immune response through macrophages infiltration [ 8 ]. Recently, macrophage polarization is confirmed to play an important role in the development of KSD [ 11 ]. However, no study has investigated the relationship between SPP1 and macrophages in KSD, which needs to be fully explored.…”
Section: Introductionmentioning
confidence: 99%